Antifungal Activities of Propolis Collected by Different Races of Honeybees Against Yeasts Isolated From Patients With Superficial Mycoses - Sibel Silici; Nedret A. Koç; Demet Ayangil; Soner Çankaya (Elsevier, 2005)
Yeasts isolated from patients with superficial mycoses were tested against propolis samples collected from different regions and honeybee races. The minimum inhibitory concentration (MIC) values obtained using the agar dilution methods were compared to the diameters of growth inhibition zones by using the disk diffusion method. The results showed that Candida albicans, C. glabrata, Trichosporon spp., and Rhodotorula sp. were susceptible to low concentrations of propolis, the latter showing a higher susceptibility. Relative to the other propolis tested, the propolis sample collected by Apis mellifera caucasica possessed the highest antifungal activity against all of the superficial mycoses. In contrast, the propolis samples collected by A.m. carnica and A.m. anatolica were the least active samples. Also, the propolis sample from the Adana region is more active than samples from other regions. An increase of MIC values was accompanied by a decrease of growth inhibition zone diameters. Keywords:: propolis, Apis mellifera L., antifungal activity, superficial mycoses